2004
DOI: 10.1007/s00455-003-0509-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Regulation During the Early Stage of Initiation of Voluntary Swallowing in Humans

Abstract: The aim of the present study was to reveal the spatiotemporal relations among cortical regions involved in the initiation of voluntary swallowing in humans using magnetoencephalography (MEG). As a control task, finger extension movement, which is purely voluntary, was also investigated using the same techniques. The swallowing-related activity was distributed widely for 2000 ms before the electromyogram onset of the right suprahyoid muscle; however, the finger-related activity occurred in the late stage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 38 publications
(51 reference statements)
2
45
1
1
Order By: Relevance
“…32 A magnetoencephalographic study demonstrated consistent long-lasting activation of the insular cortex before swallowing. 33 Taken together we posit a major role of the insula in elevating the risk of aspiration as it may function as a key area in the regulation of both voluntary and automatic swallowing.…”
Section: Neuroanatomical Predictors Of Acute Risk Of Aspirationmentioning
confidence: 84%
“…32 A magnetoencephalographic study demonstrated consistent long-lasting activation of the insular cortex before swallowing. 33 Taken together we posit a major role of the insula in elevating the risk of aspiration as it may function as a key area in the regulation of both voluntary and automatic swallowing.…”
Section: Neuroanatomical Predictors Of Acute Risk Of Aspirationmentioning
confidence: 84%
“…In the SMA, the pre-SMA receives input signals from the cingulate gyrus and the prefrontal area 17) . In addition, Watanabe et al 31) reported that the islet is closely associated with preparation of swallowing motions and that the cingulate gyrus is involved in the actual performance of swallowing; further studies using new methods will be required to confirm these results.…”
Section: Activated Brain Areas 1) Supplementary Motor Areamentioning
confidence: 99%
“…Numerous techniques have been applied to investigate functional brain activity during swallowing (primarily in healthy individuals), including positron emission tomography (PET) [31][32][33][34], magnetoencephalography (MEG) [35][36][37][38][39], transcranial magnetic stimulation (TMS) [31,[40][41][42], and electroencephalography [43][44][45] (EEG). Functional MRI (fMRI) has been especially useful in studying brain activity during swallowing in normal individuals, mainly because of its high spatial and temporal resolution (ability to detect changes in an image across different spatial locations and over time) for various tissue types, its lack of use of radiation or need for other invasive procedures (needle injections), and its ability to obtain images in any plane [46].…”
mentioning
confidence: 99%